Efeito adjuvante da propionibacterium acnes e de sua fração polissacarídica purificada sobre a imunogenicidade de vacinas para o vírus da imunodeficiência humana tipo 1 (HIV-1) - Teixeira, Daniela [UNIFESP] (2018)
After more than three decades after the discovery of the human immunodeficiency virus (HIV1), there is still no effective vaccine to control its infection. Considering the importance of CD4+ T cells in inducing an immune response that controls viral replication, a DNA vaccine encoding 18 HIV1 epitopes for CD4+ T lymphocytes (HIVBr18) was developed and showed to be capable of inducing broad, polyfunctional and long lasting response of CD4+ and CD8+ T cells in both BALB/c and HLA class II transgenic mice. However, since DNA vaccines may have suboptimal immunogenicity in humans, adjuvants play a key role in the vaccine formulation. Killed Propionibacterium acnes exerts has immunomodulatory properties extensively demonstrated in both experimental and clinical settings, such as increased phagocytic and tumoricidal activity of macrophages and the synthesis of antigenspecific antibodies. P. acnes and its soluble polysaccharide fraction (PS) were able to modulate Th1/Th2 polarization, acting directly on the antigen presenting cells, modifying the expression of costimulatory molecules, TLR and cytokine synthesis. Herein, coadministration of heatkilled P. acnes and fewer doses of HIVBr18 increased the proliferation of HIVspecific CD4+ and CD8+ T lymphocytes, the polyfunctional CD4+ T cells and the production of IFN . Moreover, there was an increase in the number of epitopes encoded by this vaccine recognized by T cells. It was shown that PS was one of the components of the bacterium responsible for most of the adjuvant effects observed. In addition, ten weeks after the last immunization, specific T cell proliferation and IFN  production were sustained in animals immunized with the bacterial suspension. In addition to the HIVspecific T lymphocyte response, neutralizing and nonneutralizing antibodies are important in protecting or controlling infection. The adjuvant effect of P. acnes on the humoral response was evident when it was associated with the recombinant protein gp140, more pronounced than when PS was, inducing high affinity antibodies directed to the Th1 response, follicular helper T cells and B cells of germinal center, in addition to inducing antibodies secreting cells. Due to the important role of CD4+ T lymphocytes in assisting the humoral response, initial immunization with the HIVBr18 vaccine was able to increase the quality of humoral response directed xxv to gp140, and when associated with P. acnes it enhanced the specific cellular response to gp140, as evidenced by the production of IFNγ and proliferation of CD4+ and CD8+ specific T cells. The adjuvant effect of P. acnes on the challenge of overcoming the genetic variability of HIV1 and the coverage of the human population was demonstrated when associated to the immunization of HLA class II transgenic mice (DR4, DQ6 and DQ8) with HIVBr18. In addition to increasing the magnitude of response in a scheme of fewer immunization doses, the breath of response was significantly increased considering the number of recognized peptides, potentiating the antigenicity and immunodominance of this vaccine, and also was able to influence the specific response to gp140 in these animals, giving rise to a higher quality humoral response together with a broad HIVspecific cellular response, targeting the majority of conserved HIV1 peptides and the viral envelope.